Medição, avaliação e modelagem de perdas de frutas e hortaliças em Uberlândia - MG - Romão, Daniela Cursino (2003)
This research conducted on municipal solid waste management for the first time quantified food spoilage as being 8.8% weight of all officially collected household garbage in the Brazilian city under study. The unexpected size of this waste fraction gave rise to work on the causes of waste and on its distribution over the product life cycle specific to fruit and vegetables. Waste was defined as being the combination of losses and scraps. Administrative shortcomings were identified as basic reasons for waste. At the producer and consumer ends of the cycle, negligence was shown to be the single most important problem. Fruit and vegetables deteriorate during the operations of handling, transport, packaging, storage, selling and consumption. The study detailed the occurrence of waste at all of these stages. In the medium-size Brazilian city, the total waste of fruit and vegetables was shown to amount to 16.6% weight in the marketing stage of the life cycle. At the consumer level, it was measured as 3.4% weight of all household garbage. Specific reasons for this waste were identified at the levels of producer, wholesaler and retailer. Short-term remedies were pointed out that invariably corrected deficient management procedures. It was shown that very simple administrative measures can significantly reduce the spoilage of fruit and vegetables. Long-term strategies involve the creation of sample cases for administration of the fruit and vegetables life cycle at all stages.